Hedge Euphemisms as Tools of Economic Discourse - E. L. Shubina (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
An attempt is made to analyze euphemized and non-euphemized versions of statements using the example of headings of short exchange messages. The relevance of the study is due to the need to study the causes and situations of the appearance of hedge euphemisms in the German language, as well as their functioning in economic discourse. The definitions, classifications and functional features of euphemisms and hedging tools in linguistics are considered. Particular attention is paid to the camouflaging function of euphemisms. The authors of the article designate euphemized statements that perform a camouflaging function with the term hedge euphemisms. The authors have collected messages (IndexCheck) of the Stuttgart Stock Exchange for investors and traders about changes in quotations from January to July 2021. It has been established that hedge euphemisms are found primarily in reports of a decline in the index. It is shown that message headers are classified depending on the presence of a component with a euphemistic coloration in them. It is noted that the ratio of euphemized and noneuphemized statements is approximately 2 : 1. It is argued that the authors of hedge euphemisms modify negative situations by resorting to the denomination process in order to mask the lexemes denoting negative situations from the point of view of investors.